2009
DOI: 10.1007/s10649-009-9216-y
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical thinking of kindergarten boys and girls: similar achievement, different contributing processes

Abstract: The objective of this study was to examine gender differences in the relations between verbal, spatial, mathematics, and teacher-child mathematics interaction variables. Kindergarten children (N=80) were videotaped playing games that require mathematical reasoning in the presence of their teachers. The children's mathematics, spatial, and verbal skills and the teachers' mathematical communication were assessed. No gender differences were found between the mathematical achievements of the boys and girls, or bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 50 publications
1
14
1
2
Order By: Relevance
“…According to sixth-grade teachers from the USA, if girls are successful, it is due to hard work, whereas boys succeed because they are bright (Jussim & Eccles, 1992). In a study focusing on gender symbols and Israeli pre-school children, mathematical success was by teachers attributed to different things depending if you talked about a girl or a boy (Klein, Adi-Japha, & Hakak-Benizri, 2010). If a boy was prosperous, the success was related to, according to these teachers, spatial ability, but if a girl was thriving, it was thought to be dependent on the girl's verbal ability.…”
Section: Introductionmentioning
confidence: 99%
“…According to sixth-grade teachers from the USA, if girls are successful, it is due to hard work, whereas boys succeed because they are bright (Jussim & Eccles, 1992). In a study focusing on gender symbols and Israeli pre-school children, mathematical success was by teachers attributed to different things depending if you talked about a girl or a boy (Klein, Adi-Japha, & Hakak-Benizri, 2010). If a boy was prosperous, the success was related to, according to these teachers, spatial ability, but if a girl was thriving, it was thought to be dependent on the girl's verbal ability.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in line with other research which found that the differences between boys and girls in the early years in mathematics performance are not significant (Klein, Adi-anales de psicología, 2014, vol. 30, nº 3 (octubre) Japha & Hakak-Benizri, 2010;Lachance & Mazzoco, 2006;Navarro et al, 2009;Navarro, Aguilar, Marchena, Alcalde and García, 2010;Van de Rijt, 1996). In Chile, the data provided by national assessments confirm that after the first cycle of elementary education there are no significant differences in achievement levels in mathematics between boys and girls, contrary to what happens at the end of secondary education, when boys have better performance than girls (MINEDUC, 2007b(MINEDUC, , 2007c.…”
Section: Discussionmentioning
confidence: 93%
“…Four papers focused on mathematics at preschool level. Klein et al (2010) studied pre-school teachers' attributions of children's achievements in mathematics, and Ojala and Talts (2007) looked at pre-school 1,2,3,3,3,3,3,3,3,3,3,3,3,4, 4 Note The number of papers is 92 a Seven European countries b Comparative study Finland and Estonia c Gender aspect: 1 structural; 2 symbolic; 3 personal; 4 interactional teachers' evaluations of achievements. Palmer (2009Palmer ( , 2010) studied pre-school teacher education when writing about alternative mathematical practices.…”
Section: Resultsmentioning
confidence: 99%